2008
DOI: 10.1371/journal.pone.0003698
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Biostatistical Analysis of CpG Island Methylator Phenotype in Colorectal Cancer Using a Large Population-Based Sample

Abstract: BackgroundThe CpG island methylator phenotype (CIMP) is a distinct phenotype associated with microsatellite instability (MSI) and BRAF mutation in colon cancer. Recent investigations have selected 5 promoters (CACNA1G, IGF2, NEUROG1, RUNX3 and SOCS1) as surrogate markers for CIMP-high. However, no study has comprehensively evaluated an expanded set of methylation markers (including these 5 markers) using a large number of tumors, or deciphered the complex clinical and molecular associations with CIMP-high dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
262
2
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 290 publications
(285 citation statements)
references
References 49 publications
15
262
2
4
Order By: Relevance
“…In one study, CpG island methylation phenotype-positive status was observed in 17% of cases with signet ring cells; however, the standard definition of signet ring cell carcinoma (450% signet ring cells) was not used in this study. 43 CpG island methylation phenotype-positive status, as defined in this study, was observed in nearly half of the signet ring cell carcinomas, and was associated with BRAF V600E mutation, but did not correlate with any clinicopathologic feature or survival. This association of CpG island methylation phenotypepositive status with BRAF V600E mutation is similar to that observed in other histologic subtypes of colorectal cancer.…”
Section: Discussionmentioning
confidence: 48%
“…In one study, CpG island methylation phenotype-positive status was observed in 17% of cases with signet ring cells; however, the standard definition of signet ring cell carcinoma (450% signet ring cells) was not used in this study. 43 CpG island methylation phenotype-positive status, as defined in this study, was observed in nearly half of the signet ring cell carcinomas, and was associated with BRAF V600E mutation, but did not correlate with any clinicopathologic feature or survival. This association of CpG island methylation phenotypepositive status with BRAF V600E mutation is similar to that observed in other histologic subtypes of colorectal cancer.…”
Section: Discussionmentioning
confidence: 48%
“…Our exon 2 KRAS mutation rate of 28% is in agreement with previous studies when mutations in exon 2 only are considered. 10,11,16,17 Like BRAF-mutated carcinomas, KRAS-mutated carcinomas showed an increased frequency of mucinous differentiation. This finding has been previously observed by Lin et al 28 and more recently by Pai et al, 8 who reported that 32% of proximal KRAS-mutated carcinoma showed mucinous differentiation compared with 25% of null carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,9 Somatic-activating mutation in the KRAS proto-oncogene is observed in 35-40% of colorectal carcinoma. 7,10,11 The overwhelming majority of KRAS mutations (90%) occur in codons 12 and 13 of exon 2, with the most frequent alteration being a G4A transition in codon 12. 12 The clinical significance of KRAS mutation in colorectal carcinoma patients is controversial; some studies reported no association with survival, 13,14 whereas others suggested that patients with KRASmutated colorectal carcinoma have poorer outcome for any mutation subtype, 15 mutation in codon 12 only 16,17 or codon 13 only.…”
mentioning
confidence: 99%
“…Although the EGFR gene is not or very rarely mutated in colorectal tumours, activating mutations of KRAS or BRAF, involved in the RAS/MAPK pathway, are present in 32-37% and in 10-17% of the cases in large population-based studies, respectively (Samowitz et al, 2000;Rajagopalan et al, 2002;Brink et al, 2003;Samowitz et al, 2005a;Nosho et al, 2008a;de Vogel et al, 2009;Ogino et al, 2009b), and mutations of PI3KCA that encodes the catalytic subunit of the PI3K protein involved in the PI3K/AKT pathway are observed in 15% of the cases (Bamford et al, 2004;Barault et al, 2008b;Nosho et al, 2008b).…”
Section: Signalling Pathways and Oncogenic Mutations In Colorectal Camentioning
confidence: 99%